Workers made idle by company strikes and the British disease - Robert A. Hart (Institute for the Study of Labor (IZA), 2009)
The strikes' literature is dominated by the causes and effects of strike action as they relate directly to strikers themselves. This paper considers another important group of affected workers - those individuals incidentally made idle as a result of the strike action of others. Using a unique data set of the British Engineering Employers' Federation (EEF), it examines the years 1960 to 1970, a critical period in Britain's postwar strikes' history. The mid-point of this decade marked the start of the era of the 'British Disease', a universally adopted title given to Britain's perceived international leadership in strikes incidence and industrial unrest. Workers made idle were an important symptom of the disease. In the study here, they accounted for 72% of days lost in disputes in which they were involved and 44% of total days lost in all disputes. Consideration is given to the likely causes of these incidental layoffs within 7130 strikes of EEF federated firms covering engineering, automotive and metal industries. Particular attention is given to the British car industry, accounting for 22% of total EEF strikes during the period of study. The regression analysis examines the causes of workers being made idle with explanatory variables covering labour market conditions, strikes durations, pay issues, non-pay issues. The regressions also control for company, union, geographical districts, annual and seasonal fixed effects.
urn:nbn:de:101:1-20090703105
Keywords: J52; L61; L62; 330; Strikes; workers made idle; pay disputes; non-pay disputes; Streik; Fehlzeit; Wirkungsanalyse; Beschäftigungseffekt; Wirtschaftliche Instabilität; Großbritannien